Preposition Stranding under Sluicing: Evidence from Hijazi Arabic - Alaowffi, Nouf; Alharbi, Bader (The journal of language and linguistic studies, 2021)
Based on data from numerous languages, such as English, Frisian, and Danish, Merchant (2001) proposes the "preposition stranding generalization" (PSG), which states that only languages that allow preposition stranding under wh-movement also allow preposition stranding under sluicing. The availability of this generalization has been the subject of a number of studies. Two contrasting views have been identified in the literature. The first view confirms the availability of the PSG in a number of different languages. The other view claims that this generalization is untenable as there exist non-preposition stranding languages that allow preposition stranding under sluicing. Our aim in this paper is to examine the availability of the PSG in the dialect of Hijazi Arabic (HA). Based on empirical data from HA on the syntactic behavior of preposition stranding under wh-movement and under sluicing, we argue that this PSG does not hold in HA. It has been observed that HA is like Emirati Arabic, Brazilian Portuguese, and Indonesian in that it disallows preposition stranding under wh-movement but allows it under sluicing. Therefore, the results of this research may contribute to the ongoing discussions on the phenomenon of sluicing in linguistic theory to help obtain a more universal analysis of this interesting ellipsis construction.